Long-term safety of OnabotulinumtoxinA treatment in chronic migraine patients: a five-year retrospective study - Navarro-Pérez, María Pilar; González-Quintanilla, Vicente; Muñoz-Vendrell, Albert; Madrigal, Elisabet; Alpuente, Alicia; Latorre, Germán; Molina, Francis; Monzón, María José; Medrano, Vicente; García-Azorín, David; González-Oria, Carmen; Gago-Veiga, Ana; et al. (Frontiers in Neurology, 2024)
Background: Real-world studies have shown the sustained therapeutic effect and favourable safety profile of OnabotulinumtoxinA (BoNTA) in the long term and up to 4 years of treatment in chronic migraine (CM). This study aims to assess the safety profile and efficacy of BoNTA in CM after 5 years of treatment in a real-life setting. Methods: We performed a retrospective chart review of patients with CM in relation to BoNTA treatment for more than 5 years in 19 Spanish headache clinics. We excluded patients who discontinued treatment due to lack of efficacy or poor tolerability. Results: 489 patients were included [mean age 49, 82.8% women]. The mean age of onset of migraine was 21.8 years; patients had CM with a mean of 6.4 years. At baseline, patients reported a mean of 24.7 monthly headache days (MHDs) and 15.7 monthly migraine days (MMDs). In relation to effectiveness, the responder rate was 59.1% and the mean reduction in MMDs was 9.4 days (15.7 to 6.3 days; p < 0.001). The MHDs were also reduced by 14.9 days (24.7 to 9.8 days; p<0.001). Regarding the side effects, 17.5% experienced neck pain, 17.3% headache, 8.5% eyelid ptosis, 7.5% temporal muscle atrophy and 3.2% trapezius muscle atrophy. Furthermore, after longer-term exposure exceeding 5 years, there were no serious adverse events or treatment discontinuation because of safety or tolerability issues. Conclusion: Treatment with BoNTA led to sustained reductions in migraine frequency, even after long-term exposure exceeding 5 years, with no evidence of new safety concerns.